HUBUNGAN ANTARA ASUPAN SERAT DAN VITAMIN C DENGAN KEJADIAN KONSTIPASI PADA MAHASISWA FAKULTAS KEDOKERAN UNIVERSITAS SWADAYA GUNUNG JATI ANGKATAN 2018 - Rhiza Mohammad Ishaq Sobari; Alya Desiana Putri; Witri Pratiwi (Fakultas Kedokteran UGJ Cirebon, 2023)
Introduction: Constipation is one of the disorders of the gastrointestinal tract which is characterized by a feeling of not defecation. Low fiber intake tends to cause constipation. This happens because a lack of fiber can result in reduced costs, causing problems to defecate. Vitamin C is a natural laxative that can help with constipation. High intake of vitamin C results in an increase in intestinal osmotic pressure, causing decreased air absorption and looser stools. Aim: To analyze the relationship between fiber and vitamin C intake with the incidence of constipation. Methods This study used an analytic observational method with a cross sectional design. Respondents were selected using simple random sampling technique, so that there were 111 students as respondents. Data collection was done by filling out a questionnaire. The data obtained were then analyzed using the Spearman correlation test. Results: The results of the analysis obtained p value = 0.097 (> 0.050) on the correlation between fiber intake and constipation. And on the correlation between vitamin C intake and constipation, the p value = 0.305 (> 0.050). Conclusion: There is no significant relationship between fiber and vitamin C intake with the incidence of constipation